Determinan intensi pelaporan pelanggaran: studi empiris pada Direktorat Jenderal Kekayaan Negara - Anton Wibisono; Faisal Faisal; Fuad Fuad (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
This study investigates the effects of whistleblowing system, organizational justice, job satisfaction on whistleblowing intention. The study surveys 113 civil servants at the Indonesian Directorate General of State Asset Management (Direktorat Jenderal Kekayaan Negara Indonesia) to generate the data. The results show that whistleblowing system and organizational justice positively affect whistleblowing intention. Thus, this study provides an empirical support to the theory of planned behavior. Further, this study contributes to the practice by suggesting that whistleblowing system and organizational justice are important factors in developing and evaluating the whistleblowing system, particularly in regard to the protection, rewards, and punishment of internal whistleblowers in public sector organizations.